The development of modern-day competences in education, in the context of an agile approach - Varga, János; Csiszárik-Kocsir, Ágnes; Garai-Fodor, Mónika (Frontiers in Education, 2025)
Our daily lives are undergoing a major transformation before our eyes. Digitalisation and digital content, social media platforms, the unlimited amount of information available on the internet, require a whole new set of people and knowledge. We need new competences to thrive that our parents and grandparents of the previous generation did not even know about. A different dimension of awareness has emerged, raising many questions from the digital, financial, consumer and sustainability perspectives. The messages and lessons from various studies and articles suggest that many individuals are not adequately prepared for these challenges, for a variety of reasons. Inherited patterns, lack of awareness-raising, some aspects of exclusion are all factors working against the process, which is also influenced by the openness, receptiveness and willingness of individuals to embrace new things. The emergence of awareness as a competence is clearly an expectation of the 21st century, without which we become very vulnerable in our challenging lives and our ability to succeed is therefore questionable. Agility as an individual competence is also a child of the 21st century. A few years ago, agility was understood more at an organisational level, but for an organisation to become agile, it needs to have agile people. Many education, training and training courses are trying to develop this approach, but the education system can also do a lot to achieve this. In this study, we analysed the generational characteristics of identification with the agile approach by processing 5,067 evaluable questionnaires in a quantitative primary research. The research found that Generation X identifies most with the agile approach. Generations Y and Z, although they have a positive view of agility, are willing and able to identify with it, but in their case there is still a strong lack of concrete knowledge and understanding. The aim of our study is to present the state of competences in modern times, including the different dimensions of awareness through the ability to be agile, in order to highlight the differences and identities in different generational, educational and other aspects, based on the results of a primary research conducted in Hungary. The literature used for this study will help to evaluate the research findings and to understand the relationship between education, agility and competences. They also help to understand why the study links these three areas, illustrate the cause and effect relationship, and in all cases studies are closely linked to the interpretation of these three areas and their impact on each other.